2022
DOI: 10.7554/elife.78277
|View full text |Cite
|
Sign up to set email alerts
|

Targeted depletion of uterine glandular Foxa2 induces embryonic diapause in mice

Abstract: Embryonic diapause is a reproductive strategy in which embryo development and growth is temporarily arrested within the uterus to ensure the survival of neonates and mothers during unfavorable conditions. Pregnancy is reinitiated when conditions become favorable for neonatal survival. The mechanism of how the uterus enters diapause in various species remains unclear. Mice with uterine depletion of Foxa2, a transcription factor, are infertile. In this study, we show that dormant blastocysts are recovered from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The gland bud phenotype is remarkably similar to gland structure observed in uteri with neonatal deletion of Foxa2 ( Fig. 4F in reference (49)). Depletion of ESR1 in the adult epithelium does not cause any quantifiable structural gland phenotypes, suggesting that epithelial ESR1 signaling during puberty is required for gland branching.…”
Section: Discussionsupporting
confidence: 75%
“…The gland bud phenotype is remarkably similar to gland structure observed in uteri with neonatal deletion of Foxa2 ( Fig. 4F in reference (49)). Depletion of ESR1 in the adult epithelium does not cause any quantifiable structural gland phenotypes, suggesting that epithelial ESR1 signaling during puberty is required for gland branching.…”
Section: Discussionsupporting
confidence: 75%
“…In that study, the authors have shown that dormant blastocysts are recovered from these mice on day 8 of pregnancy with persistent expression of uterine MSX1, a gene critical to maintaining the uterine quiescent state [17]. Interestingly, progesterone and anti-estrogen can prolong uterine quiescence [17].…”
Section: Discussionmentioning
confidence: 93%
“…A very recent study on the role of MSX1 in reproduction was carried out on mice embryonic diapause [17]. Embryonic diapause in mice is a reproductive strategy in which embryo development and growth are temporarily halted in utero to ensure neonatal and maternal survival in adverse external conditions [17]. In that study, the authors have shown that dormant blastocysts are recovered from these mice on day 8 of pregnancy with persistent expression of uterine MSX1, a gene critical to maintaining the uterine quiescent state [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forkhead box A2 (FOXA2), a member of the FOXA family, belongs to a class of transcription factors with a winged helix structure in the DNA-binding region, which performs essential roles in embryonic growth and development, cell proliferation and differentiation, glucose metabolism, airway mucus homeostasis, and lipid metabolism by binding to specific DNA sequences and activating or repressing the transcriptional activity of target genes. [11][12][13][14] The relationship between FOXA2 and tumorigenesis and tumor development has been intensively studied in recent years. Studies have documented decreased FOXA2 expression in malignant tumors, such as liver and lung tumors, which contributes to tumor proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%